PROTAGONIST’S MOTIVATION IN RACHAEL LIPPINCOTTET. AL.’S NOVEL FIVE FEET APART - Anggi Anggraini; Sri Wulan (JOURNAL OF LANGUAGE, 2020)
This study aims to reveal the protagonist’s motivation in Rachael Lippincott et. al.’s novel Five Feet Apart. This study adopts qualitative method to acquire and describe the data about the protagonist’s motivations in the novel. The discussion is divided into two sub topics concerned to the aspects of the analysis. There are two aspects of the protagonist’s motivation described in the novel. The first aspect is focused on recovery and familly’s happiness. Then, the second is about the factors which arouse the motivation. It is found in the study that the protagonist’s motivation and the factors to arouse the motivation lead to the protagonist’s success to recover and return to live with her family together.